Analisis Penetapan Harga Jual dengan Metode Cost Plus Pricing pada Dendeng Ayam Giling dengan Pengeringan Dehidrator - Rafly Pamungkas; Fitri Suciati; Rohayati Suci Indrianingsih (Universitas Galuh, 2026)
Indonesian chicken jerky is made of grounded or sliced chicken meat mixed with seasoning and spices then dried. Chicken meat was chosen to produce jerky due to its avalability and affordable price compared to beef. Generally, jerky is dried using traditional sun drying method, this research used food dehydrator for drying. The used of food dehydrator would contribute to determination of Cost of Goods Manufactured (COGM). In addition, it would also affected the selling price of chicken jerky. Tougher market competition in processed food products encourage to conduct effective selling price determination to achive profit and competitive price to compete in the market. This research aimed to determine the factors that affecting Cost of Goods Manufactured (COGM) and selling price, then further analyzed the selling price of Indonesian chicken jerky that used food dehydrator for drying. Cost-plus pricing method with a full costing approach was used to determined the selling price. Data were collected and analyzed using quantitative descriptive test. This research showed that cost of production components that involved raw material costs, direct labor cost, and factory overhead cost, included all facilities that used in production. Selling price of chicken jerky with net weight 270g was set at Rp. 30.000 per unit with 30% margin, compared to the price of other similar products this selling price are projected to be able to compete in the markets.